2013
DOI: 10.1007/s10508-012-0042-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypersexual Behavior in Frontotemporal Dementia: A Comparison with Early-Onset Alzheimer’s Disease

Abstract: The basis of hypersexual behavior among patients with dementia is not entirely clear. Hypersexual behavior may be a particular feature of behavioral variant frontotemporal dementia (bvFTD), which affects ventromedial frontal and adjacent anterior temporal regions specialized in interpersonal behavior. Recent efforts to define Hypersexual Disorder indicate an increasing awareness of heightened sexual activity as a source of personal distress and functional impairment, and clarification of hypersexuality in bvFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 48 publications
3
54
2
Order By: Relevance
“…The findings of hyposexuality in our FTD cohorts, particularly in the bvFTD group, contrasts with previous studies that have reported hypersexuality and aberrant sexual behavior in this syndrome [11,12]. This difference may be due to the fact that these studies used retrospective case note review looking for documentation of hypersexual behavior and did not look for evidence of hyposexual behavior.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The findings of hyposexuality in our FTD cohorts, particularly in the bvFTD group, contrasts with previous studies that have reported hypersexuality and aberrant sexual behavior in this syndrome [11,12]. This difference may be due to the fact that these studies used retrospective case note review looking for documentation of hypersexual behavior and did not look for evidence of hyposexual behavior.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous reports on sexual function [11,12] in FTD have highlighted the occurrence of hypersexual and aberrant sexual behavior, yet the incidence of such behavior in these studies has been rather low, between 13% [12] and 17% [11]. In the current study, we found that bvFTD is characterized by hyposexual behavior that represents a change from their behavior prior to symptom onset.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…The second type is sexually disinhibited behaviour, which is part of the general behavioural disinhibition in dementia (e.g. lewd language, exhibitionism, repeating attempts to have sex, aggressive sexual demands) [20,21].…”
Section: Search For Physical Closenessmentioning
confidence: 99%